If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(z + 2) = z + -18 Reorder the terms: 3(2 + z) = z + -18 (2 * 3 + z * 3) = z + -18 (6 + 3z) = z + -18 Reorder the terms: 6 + 3z = -18 + z Solving 6 + 3z = -18 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 6 + 3z + -1z = -18 + z + -1z Combine like terms: 3z + -1z = 2z 6 + 2z = -18 + z + -1z Combine like terms: z + -1z = 0 6 + 2z = -18 + 0 6 + 2z = -18 Add '-6' to each side of the equation. 6 + -6 + 2z = -18 + -6 Combine like terms: 6 + -6 = 0 0 + 2z = -18 + -6 2z = -18 + -6 Combine like terms: -18 + -6 = -24 2z = -24 Divide each side by '2'. z = -12 Simplifying z = -12
| x^2+(3x^2)=20 | | 5x=19.5 | | -2(5-h)=-2 | | w^2+5w-66= | | 7(y-6)=6y-16 | | 2a^2-3ab+b^2=0 | | -2(a+4)+8= | | 3+(2y+3)-4y=3 | | 180=3x+4x+40 | | ?x-2=1-2x | | .5/150= | | (9+8i)(7+i)=0 | | 25.6=8x | | p/6=9=14 | | C=0.7n+7.8 | | 10-2a=2a-6 | | 2=w/2.56 | | 5-7(10-10b)= | | an=2(1/4)^n-1 | | 15-(5m+8)=5+3m-14 | | 3x+5y=68 | | 4v/7=28 | | -5n+10=10-n | | 9(10x-9)-3= | | x+16y=202 | | x^2+1.8x-0.144=0 | | x+32+63=180 | | -4x+2(5k-6)=-3k-39 | | 7p+2(-1+7p)= | | 3(4x+2)-7x=10+3 | | 6+3*2-8-(6-4)= | | 180-48=x |